Barriers to uptake of antenatal maternal screening tests in Senegal. (December 2016) - Koster, Winny; Ondoa, Pascale; Sarr, Aïcha Marceline; Sow, Ahmad Iyane; Schultsz, Constance; Sakande, Jean; Diallo, Souleymane; Pool, Robert
Abstract: Background: Evidence exists that selective antenatal maternal screening tests contribute to the reduction of maternal morbidity and mortality. However, data are lacking on coverage with the complete set of recommended tests. The study aimed to identify barriers to uptake of the complete set of tests recommended by the Ministry of Health in Senegal. Methods: Data were collected in communities, antenatal care (ANC) clinics and the laboratories of 11 public health care facilities across Senegal. Mixed-methods included ethnography (observations and informal conversations), in-depth interviews and workshops at the health facilities; structured interviews with 283 women receiving antenatal tests ("women in the lab"); in-depth interviews with 81 women in communities who were pregnant or had recently delivered ("community women"). Results: Only 13% of community women and 22% of women in the lab had received the complete set of tests. For various social, financial and antenatal care-related reasons 38% of community women who visited antenatal care facilities did not access a laboratory. The lowest test uptake was in women receiving antenatal care at health posts. Barriers at the laboratory level were the cost of the test, stock-outs of reagents, and broken equipment. Midwives were the main gatekeepers of the laboratory, not requesting (all) tests because of assumptions about women's financial problems and reliance on clinical symptoms. Conclusion: In Senegal, recommended antenatal maternal screening tests are substantially underutilized. Efforts to increase test uptake should include accessible testing guidelines, reducing the cost of tests, raising awareness about the reasons for tests, and making the complete test set in point-of-care format accessible in peripheral health posts. National and international antenatal care policies and programs should facilitate access to maternal screening tests as a contribution to reducing maternal and infant morbidity and mortality. Highlights: Only 13% of pregnant women receive a complete set of antenatal maternal tests. Financial problems and gender relations constrain women's access to laboratories. Midwives as gatekeepers to the laboratory often request an incomplete test-set. High price, reagent stock-out and faulty machines are barriers at the laboratory. Understanding the multi-level barriers to test uptake should inform interventions.